Hydrothermal carbonization of food waste for nutrient recovery and reuse. (November 2017) - Idowu, Ifeolu; Li, Liang; Flora, Joseph R.V.; Pellechia, Perry J.; Darko, Samuel A.; Ro, Kyoung S.; Berge, Nicole D.
Highlights: Carbonization of food wastes was conducted at different times and temperatures. Leaching experiments to determine solid-phase nutrient availability were conducted. Majority of nitrogen, calcium, and magnesium remain integrated within the solid-phase. Phosphorus integration with the hydrochar increases with reaction temperature and time. Nitrogen release from the solids is small, while almost all of the phosphorus is released. Abstract: Food waste represents a rather large and currently underutilized source of potentially available and reusable nutrients. Laboratory-scale experiments evaluating the hydrothermal carbonization of food wastes collected from restaurants were conducted to understand how changes in feedstock composition and carbonization process conditions influence primary and secondary nutrient fate. Results from this work indicate that at all evaluated reaction times and temperatures, the majority of nitrogen, calcium, and magnesium remain integrated within the solid-phase, while the majority of potassium and sodium reside in the liquid-phase. The fate of phosphorus is dependent on reaction times and temperatures, with solid-phase integration increasing with higher reaction temperature and longer time. A series of leaching experiments to determine potential solid-phase nutrient availability were also conducted and indicate that, at least in the short term, nitrogen release from the solids is small, while almost all of the phosphorus present in the solids produced from carbonizing at 225 and 250 °C is released. At a reaction temperature of 275 °C, smaller fractions of the solid-phase total phosphorus are released as reaction times increase, likely due to increased solids incorporation. Using these data, it is estimated that up to 0.96% and 2.30% of nitrogen and phosphorus-based fertilizers, respectively, in the US can be replaced by the nutrients integrated within hydrochar and liquid-phases generated from the carbonization of currently landfilled food wastes.